Beyond jam sandwiches and cups of tea: An exploration of primary pupils' algorithm‐evaluation strategies. (23rd April 2018) - Benton, L.; Kalas, I.; Saunders, P.; Hoyles, C.; Noss, R.
Abstract: The long‐standing debate into the potential benefit of developing mathematical thinking skills through learning to program has been reignited with the widespread introduction of programming in schools across many countries, including England where it is a statutory requirement for all pupils to be taught programming from 5 years old. Algorithm is introduced early in the English computing curriculum, yet there is limited knowledge of how young pupils view this concept. This paper explores pupils' (aged 10–11) understandings of algorithm following their engagement with 1 year of ScratchMaths, a curriculum designed to develop computational and mathematical thinking skills through learning to program. A total of 181 pupils from 6 schools undertook a set of written tasks to assess their interpretations and evaluations of different algorithms that solve the same problem, with a subset of these pupils subsequently interviewed to probe their understandings in greater depth. We discuss the different approaches identified, the evaluation criteria they used, and the aspects of the concept that pupils found intuitive or challenging, such as simplification and abstraction. The paper ends with some reflections on the implications of the research, concluding with a set of recommendations for pedagogy in developing primary pupils' algorithmic thinking. Lay Description: What is already known about this topic: Algorithm underpins the current primary computing curriculum in England, and the concept is introduced to pupils from Key Stage 1 (age 5–7 years), but the concept is also encountered within the mathematics curriculum as part of procedural and logical reasoning. Algorithm is a foundational and complex computer science concept and has been defined in many different ways. Ideas for teaching algorithm are often based solely on expert knowledge and experience. Many pupils can experience difficulties in the understanding of algorithms but there is limited research into the nature of these specific difficulties, what features help young pupils to interpret algorithms and the criteria pupils use for evaluating similar algorithms. What this paper adds: This paper introduces an approach to teaching the concept of algorithm to primary school pupils based on a constructionist approach to learning. The research explores pupils' subsequent explanations of this concept and also the strategies and criteria they use for comparing and evaluating similar algorithms. Implications for practice: The implications of this work suggest a number of ways that the concept of algorithm can be introduced and appropriately scaffolded within the primary classroom.